Política social para a infância e adolescência: aspectos sociopolíticos nos discursos dos governadores do Paraná (1910-2010) - Freire, Mariza Scheffer (2013)
This paper analyzed the political aspects in the discourse of governors of the State of Paraná (1910-2010) when speaking on the implementation of social policies to combat the crime allegedly committed by children and adolescents. The documentary and bibliographic research enabled us to understand the economic and political context of the period between 1910 and 2010 in the State of Paraná and analyze the relationship among education, employment and public safety in that period. As a result one can see that the terminology used responded, in a way, to the national scenario. The term "minor", from the first decades of the twentieth century, has become a term that was used in the laws and documents in literature, as well as spread the messages and speeches of politicians. The early twentieth , when it began to think a poor childhood in Brazil until now, the terminology has changed , as follows: "minor orphans ", "helpless child", "vicious minor", "childhood in moral danger" , " bummers " " juvenile delinquents" , " helpless minor " , "abandoned children" , "minor bummers" , libertines" , "abandoned minors" , "perverse minor", "disadvantaged youth" , "children in need", "juvenile offender" , "disabled" , "student" , "teenager" , "teenager in Conflict with the Law